AED delivery at night – Can drones do the Job? A feasibility study of unmanned aerial systems to transport automated external defibrillators during night-time. (April 2023) - Scholz, Sean S.; Wähnert, Dirk; Jansen, Gerrit; Sauzet, Odile; Latka, Eugen; Rehberg, Sebastian; Thies, Karl-C.
Abstract: Background: In their recent guidelines the European Resuscitation Council have recommended the use of Unmanned Aerial systems (UAS) to overcome the notorious shortage of AED. Exploiting the full potential of airborne AED delivery would mandate 24 h UAS operability. However, current systems have not been evaluated for nighttime use. The primary goal of our study was to evaluate the feasibility of night-time AED delivery by UAS. The secondary goal was to obtain and compare operational and safety data of night versus day missions. Methods: We scheduled two (one day, one night) flights each to ten different locations to assess the feasibility of AED delivery by UAS during night-time. We also compared operational data (mission timings) and safety data (incidence of critical events) of night versus day missions. Results: All missions were completed without safety incident. The flights were performed automatically without pilot interventions, apart from manually choosing the landing site and correcting the descent. Flight distances ranged from 910 m to 6.960 m, corresponding mission times from alert to AED release between 3:48 min and 11:20 min. Night missions ( T ¯ m:night  = 7:26 ± 2:29 min) did not take longer than day missions ( T ¯ m:day  = 7:59 ± 2:27 min). Despite slightly inferior visibility of the target site, night landings ( T ¯ land:night  = 64 ± 15 sec) were on average marginally quicker than day landings ( T ¯ land:day  = 69 ± 11sec). Conclusions: Our results demonstrate the feasibility of UAS supported AED delivery during nighttime. Operational and safety data indicate no major differences between day- and night-time use. Future research should focus on integration of drone technology into the chain of survival.